The Role of Instructors Support and Feedback on the Performance of Online and Distance Learning - Weru, Nelson (International Journal of Online and Distance Learning, 2023)
Purpose: The purpose of this study is to explore the role of instructors support and feedback on the performance of online and distance learning. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the role of instructors support and feedback on the performance of online and distance learning. Preliminary empirical review revealed that there is need for instructors to prioritize personalized support, timely feedback, and active engagement with learners to foster a supportive and engaging learning environment. Unique Contribution to Theory, Practice and Policy: The Social Presence Theory, Self-Determination Theory and the Transactional Distance Theory may be used to anchor future studies on the role of instructors support and feedback on the performance of online and distance learning. Instructors should establish clear communication channels and responsive feedback mechanisms to facilitate ongoing interaction with learners. Instructors should provide constructive and personalized feedback that focuses on both strengths and areas for improvement. Instructors should actively foster a sense of community and social presence in online and distance learning environments. Lastly, professional development and training programs should be offered to instructors to enhance their pedagogical skills in online and distance learning